The long time performance of catalysts usually used in the literature - Vladimir D. Jović (Zaštita Materijala)
This communication discusses the “long time operation” in characterizing catalysts for the hydrogen evolution reaction (HER). It has been explained that the commonly used procedure in practically all published papers is useless and that it is necessary to define the “accelerated service life test” (ASLT) to predict the behavior of electrodes under industrial conditions. At the same time, one example of ASLT for cathodes in chlor-alkali electrolysis, obtained in our previously published papers is presented.